Peripheral Venous Plasma Aspirin Concentrations and Platelet Aggregation Inhibition Produced by Enteric-Coated Aspirin Formulations - Brandon, Roslyn A; Emmett, J A G; Eadie, M J; Curran, A C W; Bunce, I H (Thrombosis and Haemostasis, 1986)
In a random cross-over design, six healthy consenting adult volunteers were given on separate occasions single doses of 300-650 mg of 3 different formulations of enteric-coated aspirin. Over various intervals for 48-54 h following dosage, plasma aspirin and salicylate concentrations were measured together with percentage inhibition of platelet aggregation activated by threshold concentrations of sodium arachidonate alone and combined with ADP and collagen. In all subjects each formulation delivered measurable quantities of aspirin to the peripheral circulation, the unchanged drug being detected at various times up to and including 28 h after dosage. Moreover, low aspirin concentrations were found to co-exist with unimpaired platelet aggregation. All 3 formulations yielded statistically significant (P <0.01) inhibition of platelet aggregation activated both by arachidonate and by the combination of aggregants when tested 24-29 and 48-54 h after dosage; there were no significant differences (P >0.05) between the 3 formulations in this regard. Two different patterns of delivery of unchanged aspirin to the systemic circulation from these enteric-coated formulations were apparent. These patterns may be important when considering which aspirin formulation might be most appropriate in chronic use for an antiplatelet effect. None of the enteric-coated formulations used in this study may be optimal in this regard.
Keywords: Enteric-coated aspirin; Platelet aggregation; Thromboembolism